Becoming a new parent during the pandemic: experiences of pregnancy, birth, and the postnatal period - Emma Blakey; Daniel Kuria; Michelle McGillion; Fiona Scott (BMC Pregnancy and Childbirth)
Abstract New parenthood in ordinary times can be a vulnerable and unpredictable time. The Covid-19 pandemic brought additional, unprecedented changes to policy and practice that drastically impacted on the experiences of parents. This study aimed to enhance our understanding of the experiences of new parents during the pandemic by qualitatively analysing their experiences. New parents from the UK (N = 303; female = 296; male = 7) responded to a survey conducted between 2021–2022 asking about experiences of pregnancy, birth and the postnatal period. Responses were analysed thematically, taking an interpretivist approach, and drawing across the three time periods. Parents reported conflicting feelings, negative feelings and silver linings cutting across eight themes, including: impacts on well-being, feeling without a village, changes to healthcare, atypical social experiences as a new parent, differential impacts on financial and working lives, conflicting feelings around digital technology, anger and worry regarding contradictory government guidance and recommendations for other parents. The findings offer much needed insights into the experiences of new parents during this time and provide some context to the documented elevated levels of perinatal mental health difficulties in new parents during the pandemic. We suggest key recommendations going forwards in the care of new parents now, and in times of future national crisis.